Exotic magnetism in As-doped α/β-In2Se3 monolayers with tunable anisotropic carrier mobility. Issue 35 (23rd August 2019) - Li, Xiaoteng; Zuo, Xi; Li, Heming; Han, Li; Gao, Quan; Li, Dongmei; Cui, Bin; Liu, Desheng; Qu, Fanyao
Abstract : The two-dimensional (2D) material family is expanding fast as novel metal chalcogenides are being continually fabricated and intriguingly, plenty of them are ideal candidates for future nanoscale electronic and magnetic devices. Abstract : The two-dimensional (2D) material family is expanding fast as novel metal chalcogenides are being continually fabricated and intriguingly, plenty of them are ideal candidates for future nanoscale electronic and magnetic devices. Based on first-principles calculations, we investigated the electronic and magnetic properties of α/β-In2 Se3 monolayers. We find singularities of density of states appear in the valence band and hole doping (such as a Se atom substituted by a lower valence atom) can induce various ferromagnetic phase transitions in the α/β-In2 Se3 monolayers. In particular, replacement by arsenic at the anion site can enhance ferromagnetism and drive α-In2 Se3 to be a robust half-metal and β-In2 Se3 to be a bipolar magnetic semiconductor. Then, we proposed spin-polarized field-effect transistors based on α-In2 Se3 and a bipolar field-effect spin-filter based on β-In2 Se3 . Besides, we also discussed the influences of the molecules in air on the device performance such as carrier mobility. We found that the adsorption of either O2 or H2 O on α/β-In2 Se3 induced changes in hole mobility in different directions. These findings reveal a new road to electronic and magnetic modulations in 2D materials.